Grapefruit-Derived Vesicles Loaded with Recombinant HSP70 Activate Antitumor Immunity in Colon Cancer In Vitro and In Vivo - Luiza Garaeva; Elena Komarova; Svetlana Emelianova; Elena Putevich; Andrey L. Konevega; Boris Margulis; Irina Guzhova; Tatiana Shtam (Biomedicines)
Background/Objectives: Stress protein HSP70 administered exogenously has demonstrated high potential as an efficient adjuvant in antitumor immune response. To enhance the antigen-presenting activity, bioavailability, and stability of exogenous recombinant human HSP70, we propose incorporating it into plant extracellular vesicles. Earlier, we found that grapefruit-derived extracellular vesicles (GEV) were able to store the protein with no loss of its major function, chaperone activity. Methods: In this study, we tested whether HSP70 loaded into GEV (GEV-HSP70) could elicit an antitumor immune response in cellular and animal models of colorectal cancer. Results: To test the hypothesis in vitro, human and mouse colorectal cancer cell lines were used. We have shown that the addition of HSP70, either in free form or as part of GEVs, increases the sensitivity of human (HCT-116, DLD1) or mouse (CT-26) colon cancer cells to mouse cytotoxic lymphocytes and human NK-92 cells. Moreover, the amount of protein in the form of GEV-HSP70 required to cause the same activation of antitumor immunity was 20 times less than when HSP70 was added in free form. In a colon carcinoma model in vivo, GEV-HSP70 were inoculated subcutaneously into BALB/c mice together with CT-26 cells to form a tumor node. As compared with the control groups, we observed an increase in the lifespan of animals and a decrease in the tumor size, as well as a decrease in the level of TGFB1 IL-10 factors in the blood plasma. In vitro analysis of the immunomodulatory activity of GEV-HSP70 showed that antitumor response in GEV-HSP70-treated mice was associated with the accumulation of CD8+ cells. Conclusions: These results demonstrate the high feasibility and efficacy of the new technique based on HSP70 encapsulated in plant vesicles in activation of the specific response to colon tumors.